The World of Work if Female Journalists: Feminism and Professional Discrimination - Figaro, Roseli (Brazilian journalism research, 2018)
This article discuss the gender question from the feminist perspective as part of the general struggle for female emancipation in the class struggle. It addresses this perspective creating a link between the main struggles of the journalist women for a respectful place of work and labour rights and the general feminist struggle along history. The argumentative line is based on bibliographic theoretic research, investigation on women conditions and profile data, as well as on research about the work of journalists with special attention to the work of female workers in new independent labour arrangements of media conglomerates. In conclusion, this article highlights the feminist protagonism and the necessity of professional engagement in defence of quality journalism as expression and place of speech for human rights and for its emancipation.O artigo trata da discussão sobre gênero a partir do feminismo como aspecto da luta geral pela emancipação das mulheres nos embates das classes sociais. Aborda essa perspectiva traçando um elo de continuidade entre as lutas mais específicas das mulheres jornalistas por seus direitos no mundo do trabalho e a luta mais geral das mulheres trabalhadoras ao longo da história. A linha argumentativa baseia-se em pesquisa teórica bibliográfica, em pesquisa de dados sobre perfil e condições das mulheres, e em pesquisa específica sobre o perfil dos jornalistas e de seu trabalho em novos arranjos independentes dos conglomerados de meios, dando destaque à situação de trabalho das mulheres jornalistas. À guisa de conclusão, o artigo destaca a luta feminista e sua importância para a coletividade, o engajamento das profissionais em defesa do jornalismo de qualidade e como expressão e lugar de fala dos direitos humanos, pela emancipação.El articulo discute la cuestión de género tiendo el feminismo como aspecto general por la emancipación en las luchas de las clases sociales. Esta perspectiva constituye uno eje de continuidad entre las luchas más específicas de las mujeres periodistas por sus derechos en el mundo del trabajo y las luchas de las mujeres trabajadoras al largo de la historia. La argumentación esta basada en investigaciones bibliográficas, en dados sobre perfil y condiciones de las mujeres, y en investigación específica sobre el perfil de los periodistas y del trabajo del periodista en nuevos arreglos periodísticos independientes de los conglomerados de medios, con destaque para la situación del trabajo de las mujeres periodistas. En conclusión, el artículo destaca la lucha feminista y su importancia para la colectividad y también como las periodistas luchan por un periodismo de cualidad y por expresión de las voces ciudadanas por los derechos humanos y de la emancipación ciudadana.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMjUyMDAvYmpyLnYxNG4yLjIwMTguMTA1Mg